1993
DOI: 10.1111/j.1365-2559.1993.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired aganglionosis following surgery for Hirschsprung's disease: a report of five cases during a 33‐year experience with pull‐through procedures

Abstract: Acquired Hirschsprung's disease is a rare and controversial form of colonic aganglionosis. Little is known about its aetiology and pathogenesis. We report five cases encountered amongst 173 long-term follow-up patients treated for classical Hirschsprung's disease between 1957 and 1990 at the Red Cross Children's Hospital, Cape Town, and review the current literature. The clinical and pathological findings of the cases have been studied to explore possible aetiological mechanisms. Our cases, like most of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In these studies, it has been reported that biopsies of the neorectum were devoid of ganglion cells, whereas sections obtained from the proximal margin of the previous pull-through segment contained ganglion cells. Interestingly, in one of the cases reported by Cohen and associates [6], ganglion cells were present only focally in a transverse section of proximal margin, suggesting resec- Closely spaced myenteric plexus ganglia, present at the tip of the leading edge in the transition zone.…”
Section: Discussionmentioning
confidence: 82%
“…In these studies, it has been reported that biopsies of the neorectum were devoid of ganglion cells, whereas sections obtained from the proximal margin of the previous pull-through segment contained ganglion cells. Interestingly, in one of the cases reported by Cohen and associates [6], ganglion cells were present only focally in a transverse section of proximal margin, suggesting resec- Closely spaced myenteric plexus ganglia, present at the tip of the leading edge in the transition zone.…”
Section: Discussionmentioning
confidence: 82%
“…Occasional reports supported these concepts as being uncommon variants sometimes seen in association with HSCR. [35][36][37] These are of considerable interest to surgeons, both from an etiological as well as a management point of view.…”
mentioning
confidence: 99%
“…Familiarization with the mesentery vascular arcades and adequate preservation are important to avoid the poor blood supply of the PT bowel. 2,13,14 This study showed that ganglion cell loss accounted for 29.8% (n ¼ 17) of redo cases. Therefore, when the obstructive symptoms persist after PT despite conservative management, it is important to perform a preoperative workup in consideration of the possibility of ganglion cell loss and consider a redo PT.…”
Section: Discussionmentioning
confidence: 76%